Global myocardial work index predicts response to biventricular pacing in patients with non‐left bundle branch block - Shun Kondo; Yasuya Inden; Satoshi Yanagisawa; Kiichi Miyamae; Hiroyuki Miyazawa; Takayuki Goto; Masaya Tachi; Tomoya Iwawaki; Ryota Yamauchi; Kei Hiramatsu; Masafumi Shimojo; Yukiomi Tsuji; et al. (ESC Heart Failure)
Abstract Aims Cardiac resynchronization therapy (CRT) improves the prognosis of patients with heart failure (HF) and wide QRS complex. However, patients with non‐left bundle branch block (LBBB) show a poor response to CRT. This study evaluated myocardial work estimated by pressure–strain loops on echocardiography for predicting response to CRT in patients with non‐LBBB. Methods and results Of 267 patients who underwent CRT implantation, 54 patients with non‐LBBB (mean age, 62 ± 12 years, 72% males, and 24% with ischemic cardiomyopathy) were retrospectively included. Two‐dimensional speckle‐tracking echocardiography was performed before and at 6‐month follow‐up in all patients. Myocardial work was estimated by pressure–strain loop analysis using speckle‐tracking echocardiography and non‐invasive blood pressure measurement. CRT response was defined as a ≥15% decrease in left ventricular end‐systolic volume on echocardiography at the 6‐month follow‐up. The mean left ventricular ejection fraction (LVEF) before implantation was 27% ± 8% in total. Six months after implantation, 18 patients (33%) responded to CRT. The absolute LVEF improvement for responders and non‐responders were 5.5% ± 6.9% and 1.3% ± 7.5%, respectively (P = 0.021). Baseline global work index (GWI), which is the average myocardial work based on the pressure–strain loop, was significantly higher in the responder group than in the non‐responder group (590 ± 271 vs. 409 ± 216 mmHg%; P = 0.010). Multivariable analysis showed GWI to be an independent predictor of CRT response (odds ratio, 1.109; 95% confidence interval [CI], 1.013–1.213; P = 0.024). Receiver operating characteristic curve analysis determined the cut‐off value of GWI for response as 456 mmHg% (AUC 0.700, 95% CI 0.553–0.840; P = 0.019). During the median 37‐month follow‐up, all‐cause death occurred in 21 patients (39%). On multivariable analysis, GWI ≤ 456 mmHg% was independently associated with an increased risk of all‐cause mortality (hazard ratio, 2.882; 95% CI, 1.157–7.176; P = 0.023). Conclusions High GWI assessed by speckle‐tracking echocardiography and a non‐invasively estimated LV pressure curve was independently associated with a favourable response to CRT and improved outcomes in patients with non‐LBBB. The use of this non‐invasive approach for quantifying myocardial variability and residual contractility can be beneficial for assessing CRT candidates and allow for more accurate patient stratification. Further, large multicentre studies are required to validate these findings.